The Built Environment Dimensions Impact at a Winery. Issue 5 (1st September 2022) - da Silva, Marcelo Benetti Correa; Bebber, Suelen; Milan, Gabriel Sperandio; Suzin, Thais Zimmermann; Marcon, Helena Losekan; De Toni, Deonir; Da Silva, Caroline Peccin
ABSTRACT: This research goal was to analyze the built environment dimensions, namely appearance, comfort, configuration, functionality, and the relationship with customer satisfaction, service quality, and product price at a winery in Brazil. A survey was applied to customers, and data analyses were performed using Exploratory Factor Analysis to identify the dimensions and related attributes, followed by Multiple Linear Regression statistical analysis to test the relationships among the dimensions. The findings demonstrate the positive and significant impact of functionality and configuration on service quality and customer satisfaction, whereas functionality positively impacted the product price.